High Performance in Hospital Management A Guideline for Developing and Developed Countries - Weimann, Edda.; Weimann, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides a broad overview of what is needed to run hospitals and other health care facilities effectively and efficiently. All of the skills and tools required to achieve this aim are elucidated in the book, including business engineering and change management, strategic planning and the Balanced Scorecard, project management, integrative innovation management, social and ethical aspects of human resource management, communication and conflict management, staff development and leadership. The guidance offered is exceptional and applicable in both developed and developing countries. Furthermore, the relevant theoretical background is outlined and instructive case reports are included. Each chapter finishes with a summary and five reflective questions. Excellence can only be achieved when health care professionals show in addition to their medical skills a high level of managerial competence. High performance in Hospital Management assists managers of health care providers as well as doctors and nurses to engage in the successful management of a health care facility.
Engage your nurses, clinicians and patients to drive your hospital -- Create a corporate identity -- Develop your vision and communicate it -- Face your competitors -- Improve communication and appreciation -- Create positive attitudes towards change -- Develop and communicate your strategy -- Find the best staff and develop their skills -- Manage your conflicts professionally -- Be a visionary leader.
Keywords: Medicine; Health administration; Practice of medicine; Medicine & Public Health; Health administration; Practice and Hospital Management